Ultrasound-based comparative assessment of ipsilateral vs. contralateral axillary lymph nodes in breast cancer patients — a pilot study - Zenovia Antone, Nicoleta; Pintican, Roxana; Fetica, Bogdan; Lisencu, Carmen; Marian, Daria; Roman, Andrei; Trifa, Adrian; Gâta, Vlad; Muntean, Maximilian; Pop, Bogdan; Vlad, Catalin; Cadariu, Patriciu Achimaş (Frontiers in Oncology, 2025)
BackgroundAccurate axillary lymph node assessment is critical in breast cancer staging. This study aimed to evaluate whether ultrasound (US)-based measurements, particularly cortical thickness and comparison with contralateral lymph nodes, could improve diagnostic accuracy in detecting axillary metastasis.MethodsIn this prospective study, 110 breast cancer patients underwent bilateral axillary US. Ipsilateral and contralateral lymph nodes were assessed for shape, size, cortical characteristics, and hilum preservation. Quantitative features were compared between metastatic and non-metastatic nodes. Diagnostic accuracy was evaluated using ROC analysis, and various cut-off values were tested.ResultsMetastatic nodes showed significantly increased cortical thickness (median 7.5 mm vs. 2.1 mm, p<0.001), larger short axes, and irregular shapes. The cortical thickness of ipsilateral lymph nodes had an AUC of 0.967 with a 3.4 mm cut-off yielding 97.7% sensitivity and 89.1% specificity. Comparing ipsilateral and contralateral cortical thickness revealed a 2.05 mm difference as optimal (AUC 0.926, 86% sensitivity, 89.1% specificity). US-based assessment outperformed traditional imaging in accuracy (92.66% vs. 82.73%).ConclusionsQuantitative US assessment of axillary lymph nodes, especially cortical thickness and bilateral comparisons, enhances diagnostic accuracy in breast cancer. Integrating these measures may reduce unnecessary biopsies and improve staging efficiency.